Water Sensitive and Liveable Communities - Report of the National Survey on Regional and Remote Local Government Areas (LGAs) - Swapan, Mohammad; Aktar, Shamima (National Environmental Science Program (NESP), Curtin University, Monash University and CSIRO, 2024)
Amid growing concerns about water scarcity and the increasing frequency of extreme weather events, a significant shift has been reimagining Australian cities and towns as more liveable, resilient, and sustainable. As part of the National Environmental Science Program (NESP) under the Department of Climate Change, Energy, the Environment and Water (DCCEEW), researchers from Monash University, Curtin University, and the Commonwealth Scientific and Industrial Research Organisation (CSIRO) have collaborated on this project to address pressing challenges related to sustainable water management and liveability in regional, rural, and remote areas. This research contributes valuable insights that align with the Australian Government's environmental goals and strategies. The online survey was conducted between May and June 2023 to comprehend the obstacles remote and regional Local Government Areas (LGAs) face in achieving sustainable water management and liveable city outcomes. Additionally, the survey sought to identify crucial research needs that can better support these LGAs, considering their varying circumstances. The target audience comprised 400 LGAs, including 278 regional LGAs and 122 remote LGAs. From this sample, 102 valid responses were received, comprising 72 responses from regional LGAs and 30 from remote LGAs. The study focused on five thematic areas: 1) Roles, responsibilities, and functions of LGAs on urban water management and land use planning; 2) Urban water management situation in LGAs; 3) Urban Heat Management Situation in LGAs; 4) LGA’s experience, perspective and familiarity at a local level with current methods, tools and research developed for water sensitive cities and urban heat mitigation and 5) Future priorities for LGAs to achieve more sustainable water management and improved liveability.